Mortality salience and helping behavior amidst public crisis: cross-sectional evidence during COVID-19 - Xie, Qing; Yan, Yaqin; Lai, Ji; Wei, Meiting (Frontiers in Public Health, 2024)
Background As a real mortality salience, a public crisis would have a major impact on individual minds, behaviors, and lifestyles. COVID-19 provides us with a stark real-world example to understand these implications. Previous research has revealed that some individuals become more willing to help the infected at the risk of their own lives, while others become more self-centered and indifferent during COVID-19. To explain this paradoxical phenomenon, our study used two rival mediators in the relationship between mortality salience and helping behavior during COVID-19: death anxiety and death reflection. Methods A cross-sectional survey was conducted among Chinese college students (N = 684) during the pandemic. We used a parallel mediation model to explore the mediating roles of death anxiety and death reflection in the relationship between mortality salience and helping behavior during COVID-19. Results The results of our study indicate two key findings. First, mortality salience is negatively related to helping behavior during COVID-19 via death anxiety. This suggests that individuals with higher levels of mortality salience experienced increased death anxiety, which in turn led to a decrease in helping behavior. Second, mortality salience is positively related to helping behavior during COVID-19 via death reflection. This indicates that individuals with higher levels of mortality salience engaged in deeper reflection on death, which subsequently resulted in an increase in helping behavior. Conclusion Our study provides valuable insights into the complex relationship between mortality salience and helping behaviors in the time of public crisis, and can help lead to more positive attitudes toward public crisis events such as COVID-19.